2014
DOI: 10.1371/journal.pone.0089438
|View full text |Cite
|
Sign up to set email alerts
|

Mate Choice in Adult Female Bengalese Finches: Females Express Consistent Preferences for Individual Males and Prefer Female-Directed Song Performances

Abstract: In the process of mate selection by female songbirds, male suitors advertise their quality through reproductive displays in which song plays an important role. Females evaluate the quality of each signal and the associated male, and the results of that evaluation guide expression of selective courtship displays. Some studies reveal broad agreement among females in their preferences for specific signal characteristics, indicating that those features are especially salient in female mate choice. Other studies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
99
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(111 citation statements)
references
References 58 publications
10
99
2
Order By: Relevance
“…Assuming that their increased responses during the whistle treatment reflect increased arousal or even a preference for whistle songs (Searcy 1992b), we conclude that whistle songs serve in mate attraction in nightingales, a notion that had been previously proposed by several authors (e.g., Hultsch 1980;Kunc 2004Kunc , 2005aTodt and Hultsch 2006;Naguib et al 2008). Especially female vocalization behaviour during the playbacks can be seen as a strong indicator of female song preference Dunning et al 2014;Amy et al 2015). In nightingales, both sexes possess call repertoires that are used in many different situations during courtship and breeding (Horstkotte 1965;Glutz von Blotzheim 1989).…”
Section: Discussionsupporting
confidence: 67%
“…Assuming that their increased responses during the whistle treatment reflect increased arousal or even a preference for whistle songs (Searcy 1992b), we conclude that whistle songs serve in mate attraction in nightingales, a notion that had been previously proposed by several authors (e.g., Hultsch 1980;Kunc 2004Kunc , 2005aTodt and Hultsch 2006;Naguib et al 2008). Especially female vocalization behaviour during the playbacks can be seen as a strong indicator of female song preference Dunning et al 2014;Amy et al 2015). In nightingales, both sexes possess call repertoires that are used in many different situations during courtship and breeding (Horstkotte 1965;Glutz von Blotzheim 1989).…”
Section: Discussionsupporting
confidence: 67%
“…Many studies have documented the importance of male song in female mate choice (Collins, 2004; MacDougall-Shackleton, 1997; Riebel, 2009; Searcy & Yasukawa, 1996; Tomaszycki & Adkins-Regan, 2005). In some cases, song can have such a profound influence that females will solicit copulation in response to song alone, even if no male is present (Dunning, Pant, Bass, Coburn, & Prather, 2014; Nagle, Kreutzer, & Vallet, 2002; Searcy, 1992; West & King, 1988b). These data have led to the idea that males use song to advertise their attractiveness as potential mates, and females evaluate those songs and use that information to choose their mate.…”
mentioning
confidence: 99%
“…Therefore, males commonly encounter many females simultaneously. Males of those species also sing frequently throughout the day and across many different social contexts, and song is a primary means through which females select their mates (Collins, Hubbard, & Houtman, 1994; Dunning et al, 2014; Woolley & Doupe, 2008). Thus, males invest considerable time and energy in their displays to increase the number of females available for mating.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The response bias in females could be explained by mate choice preference. Dunning et al (2014) found a positive correlation between the number of calls produced by female Bengalese finches to playback of male song and the number of copulation solicitation displays, suggesting that frequency of calls reflects female preference. Moreover, they showed that each female Bengalese finch had an individual-specific song preference and the degree of selectivity for the preferred song varied across females.…”
Section: Potential and Limitations Of Habituation-dishabituation Methodsmentioning
confidence: 87%